Dual-Hormone Changes Are Related to Bargaining Performance. (June 2015) - Mehta, Pranjal H.; Mor, Shira; Yap, Andy J.; Prasad, Smrithi
In the present research, we found that endogenous testosterone and cortisol changes were jointly related to bargaining outcomes. In a face-to-face competitive negotiation (Study 1) and a laboratory-based bargaining game (Study 2), testosterone rises were associated with high earnings and high relationship quality, but only if cortisol dropped. If cortisol rose, testosterone rises were associated with low earnings and poor relationship quality. Conflict between financial and social goals was related to the financially costly dual-hormone profile (testosterone increase and cortisol increase), whereas the absence of such conflict was related to the financially adaptive dual-hormone profile (testosterone increase and cortisol decrease). The findings suggest that when cortisol decreases, rising testosterone is implicated in adaptive bargaining behavior that maximizes earnings and relationship quality. But when cortisol increases, rising testosterone is related to conflict between social and financial motives, weak earnings, and poor relationship quality. These results imply that there are both bright and dark sides to rising testosterone in economic social interactions that depend on fluctuations in cortisol.